2001
DOI: 10.1021/jp011770f
|View full text |Cite
|
Sign up to set email alerts
|

Excited State Processes in Ruthenium(II)/Pyrenyl Complexes Displaying Extended Lifetimes

Abstract: The synthesis and photophysical properties of two Ru(II) diimine complexes bearing one (dyad) and three (tetrad) pyrenyl units, respectively, are presented. The pyrene chromophore in each metal complex is tethered through a single C-C bond in the 5-position of 1,10-phenanthroline (py-phen). Both Ru(II) complexes display increased absorption cross sections near 340 nm largely due to the presence of the pyrenyl chromophore(s). Excitation from 300 to 540 nm results exclusively in the observation of metal-to-ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
129
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(143 citation statements)
references
References 30 publications
14
129
0
Order By: Relevance
“…Interestingly, its emission lifetime in water reaches 665 µs. In accordance with previous studies, this phenomenon is attributed to the emission from 3 [33][34][35][36] To study the interaction of RuPy complexes with a variety of nanotubes types (chiralities) we employed HiPco nanotubes. SWCNTs were dispersed in D 2 O solutions of either RuPy1 or RuPy2 with different initial amounts of HiPco SWCNTs.…”
Section: Resultssupporting
confidence: 74%
“…Interestingly, its emission lifetime in water reaches 665 µs. In accordance with previous studies, this phenomenon is attributed to the emission from 3 [33][34][35][36] To study the interaction of RuPy complexes with a variety of nanotubes types (chiralities) we employed HiPco nanotubes. SWCNTs were dispersed in D 2 O solutions of either RuPy1 or RuPy2 with different initial amounts of HiPco SWCNTs.…”
Section: Resultssupporting
confidence: 74%
“…[4] Out of the various organic units employed, which are appended to the ligands of the first coordination sphere, pyrene has proved to be quite effective in the tuning process of Ru II -tris(bichelating) emitters, namely [Ru(bpy) 3 ] 2+ , where bpy is 2,2Ј-bipyridine. [5] Reasons are perature and in O 2 -free solvent, complex 1 appeared to be practically nonluminescent, whereas 2 exhibited intense 3 MLCT emission; quantum yields of f em = 9ϫ 10 -4 and 6.1 ϫ 10 -2 were found for 1 and 2, respectively and λ exc = 462 nm in both cases. The lowest-lying excited states of 1 were assigned as 3 LC states, which were localised on the EP moiety.…”
Section: Introductionmentioning
confidence: 93%
“…[5,6,19,22,23] As a consequence, at room temperature (295 K), thermal equilibration between these levels can be establish according to Equation (1) (1) where N Ru /N pyr denotes the population ratio of the 3 RuLCT and 3 pyr states and ∆ TT is the energy gap between them; k B T = 205.9 cm -1 (295 K). On this basis, the luminescence properties of such bichromophores can be understood with the help of Equations (2) and (3).…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…[169][170][171] This was further developed using perylene and naphthalimide groups. [172][173][174][175][176] In the case of the naphthalimide substituents both MLCT and LC π,π* states were evident. The evidence for the LC π,π* state was elegantly demonstrated using time-resolved infrared spectroscopy in the 1400 -1800 cm -1 region which showed that the transient created in [Ru(phen)2(PNI)] 2+ was identical to that from tolyl-PNI ( Figure 10).…”
Section: Engineering New Chromophores On Ligandsmentioning
confidence: 99%